2010
DOI: 10.1186/1478-4505-8-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of methods for evaluating healthcare research economic impact

Abstract: BackgroundThe economic benefits of healthcare research require study so that appropriate resources can be allocated to this research, particularly in developing countries. As a first step, we performed a systematic review to identify the methods used to assess the economic impact of healthcare research, and the outcomes.MethodAn electronic search was conducted in relevant databases using a combination of specific keywords. In addition, 21 relevant Web sites were identified.ResultsThe initial search yielded 8,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…WHO's call reinforces the 2008 Global Ministerial Forum on Research for Health held in Mali, which recommended that each country allocate 2 % of health ministry funds to health care research (Yazdizadeh et al 2010 ). All research involving human subjects will require review by institutional review boards (IRBs) or, as they are generally known in Africa, research ethics committees (RECs) .…”
Section: Discussion Questionsmentioning
confidence: 99%
“…WHO's call reinforces the 2008 Global Ministerial Forum on Research for Health held in Mali, which recommended that each country allocate 2 % of health ministry funds to health care research (Yazdizadeh et al 2010 ). All research involving human subjects will require review by institutional review boards (IRBs) or, as they are generally known in Africa, research ethics committees (RECs) .…”
Section: Discussion Questionsmentioning
confidence: 99%
“…While the first account of the Payback Framework was in 1996 [ 29 ], a major update was described in HARPS in 2004 [ 30 ]. Two reviews of studies assessing the wider impacts from health research have been published in HARPS , one from the Italian Cochrane Centre [ 31 ] and another from an Iranian team [ 32 ], both identifying the Payback Framework as the most widely used approach, including its influence on other frameworks. Papers published in HARPS that describe applications and developments of the Payback Framework include two on primary care research in Australia [ 33 , 34 ].…”
Section: Editorialmentioning
confidence: 99%
“…The report describes various studies showing how the value of research had been demonstrated, but also quotes a review conducted in Iran [16] showing that such studies have been concentrated in high-income countries, a finding confirmed in a later review of research impact studies [17]. …”
Section: Introductionmentioning
confidence: 98%